The effect of multiple segment interaction dynamics on elbow valgus load during baseball pitching. (December 2018) - Naito, Kozo; Takagi, Tokio; Kubota, Hideaki; Maruyama, Takeo
Elbow valgus load generated in baseball pitching is a risk factor for throwing-related injuries. However, an induced acceleration analysis establishing the cause–effect relationship between elbow valgus load and causal joint kinematics is lacking. The purpose of this study was to identify the underlying mechanism of how the elbow valgus load is generated by muscular and non-muscular interactive torque effects. The throwing motions of five fastball pitches from 16 male collegiate baseball pitchers were measured by a three-dimensional motion capture system. The induced acceleration analysis developed in this study was used to separate the elbow valgus stress of the throwers into causal muscular and interactive torque components. The results showed that the shoulder internal rotation torque-induced component was greatest, accounting for 73.0% of the valgus-related contribution, while the other joint components in the muscular and interactive torque components were relatively smaller. This implied that the elbow valgus stress was highly influenced by the internal rotation torque effect, while the motion-dependent effect due to the trunk and shoulder kinematics was not influential. In conclusion, to reduce the risk of injury, pitchers should acquire proper coordination without excessive shoulder internal rotation action.